2012
DOI: 10.1002/art.34619
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal conformation and impaired degradation of propylthiouracil‐induced neutrophil extracellular traps: Implications of disordered neutrophil extracellular traps in a rat model of myeloperoxidase antineutrophil cytoplasmic antibody–associated vasculitis

Abstract: Methods. NETs were induced by treating human neutrophils with phorbol myristate acetate (PMA) in vitro. We examined whether the addition of PTU influenced the NET formation induced by PMA and the degradation of NETs by DNase I, which is regarded as a regulator of NETs. Furthermore, we examined whether NETs generated by the combination of PMA and PTU induced MPO ANCA and MPO AAV in vivo in rats.Results. When NETs were induced by PMA with PTU using human neutrophils in vitro, abnormal conformation of NETs was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(167 citation statements)
references
References 23 publications
6
158
0
3
Order By: Relevance
“…The most popular method to quantify NETs is the image analysis, which is based on fluorescent staining using DAPI 10, 16, 17. To determine the equivalence in quantification of the flow cytometric detection of neutrophils that formed NETs using SYTOX Green to the image analysis, we compared the two methods.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular method to quantify NETs is the image analysis, which is based on fluorescent staining using DAPI 10, 16, 17. To determine the equivalence in quantification of the flow cytometric detection of neutrophils that formed NETs using SYTOX Green to the image analysis, we compared the two methods.…”
Section: Resultsmentioning
confidence: 99%
“…NETs trap and kill microbes, including bacteria, fungi and protozoa (3,(10)(11)(12)(13)(14) but have also been connected to various autoinflammatory or autoimmune diseases, such as preeclampsia, systemic lupus erythematosus (SLE), Felty´s syndrome (FS) and rheumatoid arthritis (RA) (15)(16)(17)(18)(19). NETs have also been suggested to be important in a rodent model of drug-induced vasculitis (20), implying a role of NETs in the pathogenesis of AAV as well. Further, increased levels of NETosis-derived products (or NET remnants) in the circulation have been reported in a small number of patients with active vasculitis (2).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that propylthiouracil given to NETosing PMNs resulted in disordered NETs, which were resistant to DNase and had the ability to induce vasculitis in rodents. 109 Systemic lupus erythematosus (SLE, lupus) is a complex autoimmune disease, comprising a constellation of clinical manifestations of unknown cause. In addition to important clinical features, serological testing often reveals high levels of antinuclear antibodies and anti-double-stranded DNA antibodies.…”
Section: Autoimmune and Vasculitic Diseasementioning
confidence: 99%